Initial growth of zinnia seedlings in substrate with different proportions of biosolid - de Souza, Antonio Maricélio Borges [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; Sgobbe, Giovana [UNESP]; Ferreira, Kássia Barros [UNESP]; Campos, Thiago Souza [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2022)
Zinnia (Zinnia elegans Jacq.) is a widely cultivated species and used as an ornamental plant in the world flower market. Although it has great potential for phytoremediation and compounds with anti-infective and antioxidant activities there are few studies that address the process of production of its seedlings especially using substrates from organic waste. This study aimed to evaluate the potential of biosolid as a substrate component in the initial growth of Zinnia elegans seedlings. The seedlings were produced in nursery conditions with 50% light control. The experimental design was entirely randomized. There were six treatments, four repetitions and five plants per plot. The treatments consisted of substrates resulting from the mixture of subsoil (SS) and biosolid (BIO) in different proportions: 100% SS (control); 80% SS + 20% BIO; 60% SS + 40% BIO; 40% SS + 60% BIO; 20% SS + 80% BIO; T6 100% BIO. The morphological and quality characteristics of the seedlings were evaluated. Polynomial regression analysis and Pearson correlation coefficient were performed. Quadratic regression fitting was observed for plant height, stem diameter, leaf area, total chlorophyll, and shoot and root dry mass, as well as total dry mass. The shoot height/stem diameter ratio was the characteristic that correlated least with the others, being observed a positive correlation only with plant height. The use of biosolid in the proportion of 60% in the substrate composition proved to be efficient for the initial growth of seedlings as it showed the best responses for most morphological and quality characteristics of the seedlings.
Crescimento inicial de mudas de zínia em substrato com diferentes proporções de biossólido
Keywords: composto orgânico; lodo de esgoto; mudas de qualidade; organic compost; ornamental plant; planta ornamental; quality seedlings; sewage sludge; Zinnia elegans